Mata Golo, the Ke'o Rado Ritual, and The Death of Jesus Christ on The Cross in the Perspective of the Ngada People in Central Flores Indonesia - Paskalis Lina; Raymundus I Made Sudhiarsa (P3TK, Sanata Dharma University, 2022)
Most traditional societies have different conceptions of death and dying. The people of Ngada in Central Flores have a conception of death and dying called ‘mata golo.’ Mata golo is a bad death or a bloody death. This kind of death is caused by, for instance, a natural disaster, being killed by others, being killed in a traffic accident, etc. This article presents a theological inculturation view of the death of Christ on the Cross as a sign of reconciliation and peace in the perspective of mata golo among the Ngada people and in that of the ke’o rado ritual that follows it. This ritual is meant to bring about reconciliation and establish peace between the members of the clan on the one hand and the dead and the ancestors on the other hand. By using the inculturation method, we first listen to the culture. For this, the qualitative research method is used by conducting field research observations, in-depth interviews with key informants, and literature studies of previous studies on mata golo. The result is then compared with the teachings and views of the Catholic Church on the death of Christ. These two themes are then synthesized to build a distinctive theological concept, which could be a contribution to future pastoral services.